A fence barrier method of leading edge cell capture for explorative biochemical research. Issue 5 (3rd September 2017) - Wager, Lucas J.; Murray, Rachael Z.; Thompson, Erik W.; Leavesley, David I.
ABSTRACT: The scratch or wound-healing assay is used ubiquitously for investigating re-epithelialisation and has already revealed the importance of cells comprising the leading edge of healing epithelial wounds. However it is currently limited to studying the effect of known biochemical agents on the tissue of choice. Here we present an adaptation that extends the utility of this model to encompass the collection of cells from the leading edge of migrating epithelial sheets making available explorative biochemical analyses. The method is scalable and does not require expensive apparatus, making it suitable for large and small laboratories alike. We detail the application of our method and exemplify proof of principle data derived from primary human keratinocyte cultures.